(Con)Vivendo com mães e madrastas: o encontro de papéis sob a percepção do filho(a) - Coppola, Heloisa De Lucca Nobre (2019)
New family configurations are becoming more diverse when considering divorce and the need for new love relationships. At the same time, the number of new members participating in the daily life, the tasks and care of the children born in the first union, such as the stepmother and the stepfather, increases. When the father's family nucleus remarries, the stepmother becomes a new member of the newly formed system and although mothers and stepmothers have differentiated relational space, they perform similar care functions. The children, in turn, circulate between the two families, intermediate the relations of the family members that compose the multinuclear system carrying interferences, interfering and directly facing the conflicts of loyalties. This study has realized a qualitative research with the children born in the first marriage, to know what their perception of the reality lived within a multinuclear family, what elements exist between these three participants and what the meaning attributed to the experience lived. The Genogram and the semi interview - structured were the instruments used for data collection, whose purpose was to understand the meaning of the narratives of the participants. The results were categorized and submitted to a content analysis to understand the reality of the children who experience this family context. The information obtained aims to cooperate in the work of therapists who care for families and often find themselves faced with a competitive and conflicting reality